A Comparison of Interactions Among Children, Parents, and Therapists in Cognitive Behavior Therapy for Anxiety Disorders in Australia and Japan. Issue 1 (January 2022) - Ishikawa, Shin-ichi; Romano, Mia; Hudson, Jennifer L.
Highlights: The study examined cultural differences during CBT for youth anxiety. We compared therapeutic interactions in CBT sessions between Australia and Japan. Therapeutic interactions were compared using a novel behavioral coding system. Therapeutic interactions differed between countries across first and last sessions. Therapeutic interactions predicted anxiety treatment outcome at posttreatment. Abstract: Despite growing attention to the efficacy of culturally adapted cognitive-behavioral treatment (CBT) programs for children and adolescents, there is still little empirical and practical information available to therapists who adapt original treatment protocols to suit clients of a specific culture. The current study aimed to compare therapeutic interactions across CBT treatment delivered with two different cultural groups. We developed an observational coding system to examine behaviors exhibited by child, parent, and therapist during CBT sessions conducted in Australia and Japan for children with anxiety disorders. Our results demonstrated significant differences between the two countries with respect to the treatment readiness of children, the proportion of talking during the sessions by parents and children, therapists' laughter, length of silence during the first session, and parent indices of accommodation. In terms of transitions over time (i.e., first to last CBT session), parents in both countries tended to talk more during the last CBT session, whereas only Australian therapists talked less over time. The proportion of silence decreased over time during the Japanese sessions, and the amount of interruptions by parents increased over time for Australian sessions. Finally, our exploratory analyses demonstrated that a number of behavioral observations were correlated with anxiety treatment outcome at posttreatment. This study suggests that interactions between a child, parent, and therapist during CBT sessions may be affected by the culture in which the CBT session occurs, which could have implications for culturally adapted CBT programs.